Under Two Patriarchal Authorities? Subordination of Female Peacekeepers by Husbands and the State: A Feminist Critique - Febrie Fitria Nabilaputri; R. Widya Setiabudi Sumadinata; Wawan Budi Darmawan (Ilomata International Journal of Social Science, 2026)
This research examines dual subordination of Indonesian female peacekeepers experiencing layered control from private institutions (family/husbands) and public institutions (state/military). Using critical feminist methodology through qualitative literature-based discourse analysis, this study applies feminist state theory and intersectionality analysis to reveal how the state instrumentalizes marriage institutions controlling female soldiers' professional autonomy. Findings indicate spousal permission requirements for peacekeeping assignments create dual ownership: women belong to husbands privately and the state publicly, making career advancement contingent on spousal approval rather than solely professional competence. Three operational mechanisms function: juridical domestication (codifying marital status as professional determinant), institutional collusion (domestic-military patriarchy collaboration), and internalized patriarchy (women accepting subordination systems). Comparative analysis reveals male soldiers face no equivalent requirements, perpetuating hegemonic masculinity. This study offers a new analytical framework conceptualizing dual ownership through three subordination mechanisms for understanding spousal-permission regulations in troop-contributing countries, advancing knowledge on domestic-institutional patriarchy intersections limiting women's peacekeeping participation.